UPAYA DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN KUANTAN SINGINGI DALAM MEWUJUDKAN DESTINASI PARIWISATA UNGGULAN TAHUN 2017-2018 - Hardiwirasukma, Gita; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Ministry of Culture and Tourism of Kuantan Singingi has a crucial role, especially in tourism development and cultural preservation. In order to accelerate the development of tourism destinations with the issuance of the Decree of Kuantan Singingi Regency Number: KPTS 11/25/2017, it is necessary to establish a flagship tourism destination which requires integrated, comprehensive and sustainable steps in their realization. However, in fact, the purpose of Kuantan Singingi Regent is difficult to materialize because the Ministry of Culture and Tourism has not been serious in developing the tourism destinations. The formulationof the problem in this study were (1) how is the effort of Ministry of Culture and Tourism of Kuantan Singingiin realizing the flagship tourism destinations in 2017-2018? (2)what are the inhibiting factors in the efforts of the Ministry of Culture and Tourism of Kuantan Singingi in realizing the flagship tourism destinations in 2017-2018?This study aimed to (1) describe the efforts of the Ministry of Culture and Tourism of Kuantan Singingi in realizing flagship tourism destinations in 2017-2018, (2) describe the inhibiting factors of Ministry of Culture and Tourism of Kuantan Singingi’sefforts in realizing flagship tourism destinations in 2017 2018. This research was a descriptive study with a qualitative approach. This study was conducted at the Ministry of Culture and Tourism of Kuantan Singingi. The data was collected through interviews and documentation. The data analysis technique used was an interactive analysis model. The study concluded that the efforts of the Ministry of Culture and Tourism of Kuantan Singingi in realizing flagship tourism destinations in 2017-2018 were seen through the role of entrepreneurs, the role of coordinators, the role of facilitators and the role as stimulators that were not optimal. The efforts of Ministry of Culture and Tourismwere influenced by internal factors and external factors. The internal factors werebudget constraints, inadequate human resources and regulations; the absence of regional regulations related to the Regional Tourism Development Master Plan of Kuantan Singingi. Meanwhile, theexternal factors were the lack of community participation in tourism destinations development and the low involvement of the private sector in developing tourism destinations.Keywords: Efforts, Development Acceleration, Flagship Tourism Destinations